(untitled) (Szociológiai Szemle, 2024)
In this paper we investigated how workers’ opinion about the importance of secure job has changed during the transition and also how workers’ evaluation about job security was modified. Finally, we have attempted to assess the effect of job security on job satisfaction. Data were taken from the International Social Survey Program (ISSP) Work Orientation Module from 1989 and 1997. Our results, which have been derived by using the ordered logit model, show that employees perceive their work to be less secure in the post-transition period. This view is generally held among workers, but the decrease in perceived job security differs among worker groups. The differences reflect the actual labour market position and the change in this position as we expected. As far as the importance of job security is concerned, our results show that a positive relationship exists between the importance of high pay and the importance of job security. Moreover, this relationship was stronger in 1997 than in the pre-transition subsample. We take this result as evidence supporting our hypothesis about changing worker strategies for achieving high pay. Finally we investigated the effect of perception of job security on job satisfaction. Indeed, the perception of job security, together with other perception variables, as high pay or promotion opportunities, proved to be strongly influencing responses to job satisfaction, with experiences o f high pay having the largest (and increasing) effect.